1998
DOI: 10.1007/s004060050020
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological impairment and psychopathology in first-episode schizophrenic patients related to the early course of illness

Abstract: The objective of the present study was to explore whether the early course of illness including first onset of psychotic symptoms influences neuropsychological functioning and psychopathology in first-episode schizophrenics. Patients with a short prodromal period (n = 20) and patients with a long prodromal period (n = 20) and controls matched with regard to age, gender and education (n = 40) were administered a battery of standardized neuropsychological tests and psychopathological rating scales. The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 38 publications
2
16
0
2
Order By: Relevance
“…We found that first-episode schizophrenic patients generally performed much worse on neuropsychological tests than controls, supporting existing evidence that their impairments in neurocognitive functions extend across multiple domains [Hoff et al, 1992;Bilder et al, 1992aBilder et al, , 2000Binder et al, 1998;Mohamed et al, 1999;Albus et al, 2002;Moritz et al, 2002;Addington et al, 2003;Ho et al, 2003]. Our results show that neurocognitive impairments exist in schizophrenic patients at the very early stage of illness, and imply that such deficits represent proxy measures of the primary pathology of schizophrenia.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that first-episode schizophrenic patients generally performed much worse on neuropsychological tests than controls, supporting existing evidence that their impairments in neurocognitive functions extend across multiple domains [Hoff et al, 1992;Bilder et al, 1992aBilder et al, , 2000Binder et al, 1998;Mohamed et al, 1999;Albus et al, 2002;Moritz et al, 2002;Addington et al, 2003;Ho et al, 2003]. Our results show that neurocognitive impairments exist in schizophrenic patients at the very early stage of illness, and imply that such deficits represent proxy measures of the primary pathology of schizophrenia.…”
Section: Discussionsupporting
confidence: 87%
“…Studying neuropsychological function at an early stage of the illness has the advantage of precluding such confounding effects. Moreover, research based on drug naïve schizophrenic patients also avoids the confounding effects of short term use of medications [Hoff et al, 1992;Bilder et al, 1992aBilder et al, , 2000Binder et al, 1998;Mohamed et al, 1999;Albus et al, 2002;Moritz et al, 2002;Addington et al, 2003;Ho et al, 2003]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that schizophrenic patients in psychotic states (Binder et al 1998) and in remission (Wohlberg & Kornetsky 1973) as well as high-risk samples (Nuechterlein 1983;Erlenmeyer-Kimling 1987) have deficits in CPT performance. Furthermore, CPT measures seem to be related to schizophrenic psychopathology (Nuechterlein et al 1986;Strauss et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Binder et al (21) reported no difference in neuropsychological performance between patients with short and long prodromal periods, suggesting that neuropsychological deficits in first-episode schizophrenia are independent of the early course of the illness. DeQuardo et al (22) associated premorbid asociality with adult neuropsychological dysfunction, and Levitt et al (23) reported an association of poor premorbid adjustment with perseverative errors on the Wisconsin Card Sorting Test and poor visual memory span performance.…”
mentioning
confidence: 99%
“…Some have found an association of neurocognitive deficits with negative symptoms (6,(25)(26)(27), others have not (9,21).…”
mentioning
confidence: 99%